Muscle Cell and Tissue - Sakuma, Kunihiro (IntechOpen, 2015)
In order to complete tissue regeneration, various cells such as neuronal, skeletal, smooth, endothelial, and immune (e.g., macrophage) interact smoothly with each other. This book, Muscle Cells and Tissues, offers a wide range of topics such as stem cells, cell culture, biomaterials, epigenetics, therapeutics, and the creation of tissues and organs. Novel applications for cell and tissue engineering including cell therapy, tissue models, and disease pathology modeling are discussed. The book also deals with the functional role of autophagy in modulating muscle homeostasis and molecular mechanism regulating skeletal muscle mass. The chapters can be interesting for graduate students, postdocs, teachers, physicians, and for executives in biotech and pharmaceutical companies, as well as researchers in the fields of molecular biology and regenerative medicine.